Pengembangan Game Pembelajaran Menggunakan Platform Wordwall pada Tema 3 Makananan Sehat Kelas V Sekolah Dasar - Wisry Dona Ernita; Novrianti Novrianti; Zuwirna Zuwirna; Ade Meldi (Journal on Education, 2023)
With the current learning conditions that are increasingly advanced, students need supporting learning media, namely flexible learning media that students can access without having to be in the classroom. However, the use of learning media is still lacking and limited, especially technology-based learning media such as learning games. Learning games using Wordwall can help teachers develop instructional media that students can practically access outside of the classroom. The goal achieved in this study is to determine the feasibility and practicality of the learning game. This type of research is Research and Development (R&D). The development model used in this study is the ASSURE model which has 6 stages of development, namely analyze learner, state objectives, select instructional method, utilize media and materials, require learner participation, evaluate and revise. The results of the validity test of learning game media by media expert I are categorized as "Very Valid" with the highest score of 5 and the lowest score of 4, getting a total of 53 points with an average of 4.81. Meanwhile, media expert II's media validity assessment data is also categorized as "Very Valid" with the highest score of 5 and the lowest score of 4, the total number of points is 54 with an average of 4.90. As well as the practicality test results of this learning game in the "Very Practical" category by obtaining a total score of 963 out of a maximum score of 1,000, an average score of 4.8. Development of learning games using the Wordwall platform on Theme 3 Class V Elementary Schools is appropriate for use as a learning medium and supports the learning process.